2023
DOI: 10.52082/jssm.2023.117
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Accelerometer Epoch Length on Associations of Physical Activity Intensity and Volume with Bone Outcomes

Abstract: Two accelerometer metrics (intensity-gradient and average-acceleration) can be used to determine the relative contributions of physical activity (PA) volume and intensity for health, but it is unknown whether epoch length influences the associations detected. This is important when considering bone health, as bone is particularly responsive to high intensity PA, which may be underestimated by longer epochs. This study aimed to assess the associations between average-acceleration, a proxy measure of PA volume, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…62,63 Moreover, associations of MVPA with sociodemographic factors and health outcomes do not vary with epoch length. [64][65][66] Therefore, the variation in prevalence of physical inactivity we found would likely be similar, even with different epoch lengths. Lastly, a systematic review suggested that the protective effect of device measured PA on mortality plateaus around 130 to 140 minutes per week.…”
Section: Discussionmentioning
confidence: 82%
“…62,63 Moreover, associations of MVPA with sociodemographic factors and health outcomes do not vary with epoch length. [64][65][66] Therefore, the variation in prevalence of physical inactivity we found would likely be similar, even with different epoch lengths. Lastly, a systematic review suggested that the protective effect of device measured PA on mortality plateaus around 130 to 140 minutes per week.…”
Section: Discussionmentioning
confidence: 82%
“…We also used 15 s epochs rather than the 5 s epochs that were used when the IG was initially designed [4]. This may have contributed to the lower IG seen with the count IG, as previous work has shown that as the epochs' size increases, the IG becomes shallower [26]. Furthermore, the lowest intensity bins in the adjIG likely differed in the nature and range of activity compared with the accIG, as the adjIG bins included more values above the sedentary threshold than the first bins in the accIG.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies of adolescents, PA is usually investigated in relation to health, and the most meaningful PA indicators are not only vigorous activities, but also energy expenditure, moderate-to-vigorous activity, and sedentary hours ( Joensuu et al, 2018 ; Papadopoulou et al, 2021 ; Skinner et al, 2023 ; Wang et al, 2019 ). This study also analyzes PA as part of a project to investigate the impact of youth athletes’ lifestyle on their growth and development, so in future research, it might be better to consider both of a short epoch that can better capture physical movements and a long epoch that can better reflect physiological energy expenditure levels.…”
Section: Discussionmentioning
confidence: 99%